SIGNIFICANT FEATURES OF THE STRUCTURE OF EMOTIONAL SENTENCES - Darmon Saidaxmedovna, Uraeva; Kaharova Sidikovna, Iroda (International Journal of Psychosocial Rehabilitation, 2020)
Emotional speech, linguistic, logical, and spiritual activities are interconnected, reflecting the process of speaking in a specific way, which again proves that language is not only a means of moving the mind but also affecting the spirit. In this sense, linguistic emotion is recognized as one of the distinctive linguistic structures of speech.Emotional sentences are primarily a linguistic activity and its product. The emotional and psychosocial factors are also influenced by the emotional expression of psychology (which represents different mental emotions of a person) and sociological (which can be a form of social communication, a means of interpersonal communication). The main purposes of emotional sentences are communication, communication interference, and transferring ideas, and they help to express different emotions. By its structure, it is often one component. They have a number of repetitions of the word that emphasizes empathy to enhance emotionality. Its construction is sometimes based on inversion. The end of the note is marked with an exclamation mark, and its use takes into account the strength or weakness of the tone.